(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
In a today’s modern market scenario and ever-increasing load of Human Resource Management, it is important that prospective of human resources be explored to the best for development of organization. Since, last few decades the systems and procedures of work in Human Resource management have been changing, from operational management systems to strategic one with the help of analytics. One of the noteworthy tasks of authorities of human resource is talent acquisition process, so to bring together the information on HRA for recruitment, done a organized literature review and analysis of information gathered. Total of 63 research studies have been studied and for the present review considered 30 for consequent information investigation. While the outcomes give one hand information on HRA in talent acquisition process and the comparative inventiveness of the field of HRA, with the mainstream of the studies done so far.